Migra????o de c??lulas precursoras miog??nicas sob a influ??ncia de sobrenadantes de macr??fagos irradiados com laser de baixa pot??ncia - Batista, ??rika C??ssia Barroso (2015)
The activation, proliferation and migration of myogenic precursor cells are essential for muscle regeneration after injury, orchestrated by cells and local components, mainly inflammatory cells, especially macrophages. These are identified as a target for the treatment of muscle injuries. Laser therapy has shown good results in treatment of injuries and the ability to accelerate the migration of various cell types, but there are no reports on their effect on macrophage products influencing the migration of myogenic precursor cells. The aim of the study was to evaluate the effect of low level laser (LLL) on migration of myoblasts cultured with macrophage culture supernatants of different phenotypes. Therefore, C2C12 cells were cultured with supernatants from cultures of macrophages (J774) treated with LPS and IFN-?? (for the activation phenotype M1), IL-4 (M2a phenotype) and IL-10 and dexamethasone (M2c phenotype) and LLL irradiated at wavelengths of 660nm and 780nm (70mW; 17,5J / cm2; 14.3 s; 0,8J). Supernatants from macrophage cultures were harvested 24h after irradiation and transferred to myoblast cultures. Migration was assessed using the scratch assay and the results statistically analyzed. Myoblasts cultured with phenotype macrophage supernatants M2c and irradiated with LBP (660nm) showed higher migration capability that cultured with supernatants of M2C phenotype of macrophages after 12 hours of cultivation. There was no difference between the other groups. The LLL was able to modulate the migration of myoblasts C2C12 when M2c supernatants of macrophage phenotype